Degradation of Chloroaromatics: Purification and Characterization of a Novel Type of Chlorocatechol 2,3-Dioxygenase of Pseudomonas putida GJ31 - Kaschabek, Stefan R. (American Society for Microbiology, 1998)
A purification procedure for a new kind of extradiol dioxygenase, termed chlorocatechol 2,3-dioxygenase, that converts 3-chlorocatechol productively was developed. Structural and kinetic properties of the enzyme, which is part of the degradative pathway used for growth of Pseudomonas putida GJ31 with chlorobenzene, were investigated. The enzyme has a subunit molecular mass of 33.4 kDa by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Estimation of the native M(r) value under nondenaturating conditions by gel filtration gave a molecular mass of 135 ± 10 kDa, indicating a homotetrameric enzyme structure (4 × 33.4 kDa). The pI of the enzyme was estimated to be 7.1 ± 0.1. The N-terminal amino acid sequence (43 residues) of the enzyme was determined and exhibits 70 to 42% identity with other extradiol dioxygenases. Fe(II) seems to be a cofactor of the enzyme, as it is for other catechol 2,3-dioxygenases. In contrast to other extradiol dioxygenases, the enzyme exhibited great sensitivity to temperatures above 40°C. The reactivity of this enzyme toward various substituted catechols, especially 3-chlorocatechol, was different from that observed for other catechol 2,3-dioxygenases. Stoichiometric displacement of chloride occurred from 3-chlorocatechol, leading to the production of 2-hydroxymuconate.